NEROLIDOL, KOMPONEN KIMIA AROMATIK TANAMAN TEH YANG JUGA DIPRODUKSI OLEH JAMUR ENDOFIT Schizophyllum sp. D [Nerolidol, an Aromatic Chemical Constituent of Tea Plant that Produce by an Endophytic Fungi Schizophyllum sp. D] - Agusta, Andria (BERITA BIOLOGI, 2013)
Cultivation of an endophytic fungus Schizophyllum sp.D, isolated from a tea plant Camellia sinensis (L.) O.K. in liquid medium PDB, on a rotary shaker at 100 rpm at room temperature (26 - 30 oC) produced a major metabolite with a production capacity of 56.7 mg/L. Structure elucidation based on MS, NMR spectra and published data showed that metabolite is nerolidol. This chemical compounds is one of important aromatic chemical constituent that contribute to tea aroma and defense system in a tea plant.